2017
DOI: 10.1007/s13300-017-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of 50/50 Premixed Insulin Analogs in Type 2 Diabetes: Systematic Review and Clinical Recommendations

Abstract: IntroductionPremixed insulin analogs represent an alternative to basal or basal–bolus insulin regimens for the treatment of type 2 diabetes (T2D). “Low-mix” formulations with a low rapid-acting to long-acting analog ratio (e.g., 25/75) are commonly used, but 50/50 formulations (Mix50) may be more appropriate for some patients. We conducted a systematic literature review to assess the efficacy and safety of Mix50, compared with low-mix, basal, or basal–bolus therapy, for insulin initiation and intensification.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
(168 reference statements)
0
4
0
Order By: Relevance
“…The prevalence of diabetes and prescription patterns of glucose-lowering agents differs across countries. For example, the most preferred treatment routine is basal-bolus in Australia but pre-mixed insulin in Saudi Arabia [ 14 , 15 ]. Consequently, it is important to ascertain the clinical parameters associated with the use of IDegAsp in diverse geographical settings.…”
Section: Rationalementioning
confidence: 99%
“…The prevalence of diabetes and prescription patterns of glucose-lowering agents differs across countries. For example, the most preferred treatment routine is basal-bolus in Australia but pre-mixed insulin in Saudi Arabia [ 14 , 15 ]. Consequently, it is important to ascertain the clinical parameters associated with the use of IDegAsp in diverse geographical settings.…”
Section: Rationalementioning
confidence: 99%
“…A randomized study performed by Chen et al showed that insulin mixtures containing 50% of the fast-acting analogue are much more effective in treating patients using higher carbohydrate diets [62]. This is reflected in the summary of clinical recommendations on the use of insulin mixtures in the treatment of type 2 diabetes, indicating that in some patients Mix50 mixtures may be more appropriate than Mix25/30 mixtures, and clinicians should consider not only efficacy and safety, but also traits and patient preferences during insulin treatment of people with type 2 diabetes [63].…”
Section: Insulin Therapy In People With Type 2 Diabetesmentioning
confidence: 99%
“…They should also be asked for preference regarding injection frequency and blood glucose monitoring. In addition, costs should be discussed to make the therapy affordable in the long term [ 33 ]. Continuous support and guidance from the treating physician can help combat patient fears and doubts and reduce the possibility of ‘psychological insulin resistance’ [ 34 , 35 ].…”
Section: Factors Influencing Choice Of Premixed Formulationsmentioning
confidence: 99%